Neglected tropical diseases caused by tapeworm infections - Harrison, Wendy (Henry Stewart Talks, 2022)
Tapeworm infections resulting in neglected tropical diseases, Taeniasis, Cysticercosis, Neurocysticercosis, Cystic echinococcosis, Hydatid disease, Impact of tapeworm infections on communities and economies, Diagnosis and treatment of tapeworm infections, Control and prevention of tapeworm infections